Design parameters study of an intelligent air-cushion tracked vehicle - Rahman, Mohammed Ataur; Hossain, Altab (Canadian Society for Mechanical Engineering, 2011)
The aim of this paper is to present the design parameters study of a developed intelligent air-cushion tracked vehicle (IACTV) for swamp peat terrain in Malaysia. The prototype parameters for a track system including track width and ground contact length and a novel design auto adjusting air-cushion system are incorporated by accounting the kinematics and dynamics behaviors of the vehicle to ensure good tractive performance. The vehicle track width and ground contact length affect the vehicle motion resistance significantly. The air-cushion system significantly reduces total motion resistance and thus power consumption. The experiment and simulated performance results such as motion resistance coefficient of 3-7 % and the tractive efficiency of 60-72 % for the vehicle slippage of 3-10 % indicate that the developed vehicle can meet the swamp peat terrain requirement with its optimal power consumption.